Probiotics and prebiotics - Gibson, Glenn (Henry Stewart Talks, 2011)
The human large intestine is an intensively colonised area containing bacteria that are health promoting, as well as pathogenic, This has led to functional food developments that fortify the former at the expense of the latter, Probiotics have a long history of use in humans as live microbial feed additions, In contrast, a prebiotic is a non digestible food ingredient that beneficially affects the host by targeting indigenous components thought to be positive, Dietary carbohydrates, such as fibres are candidate prebiotics but most promise has been realised with oligosaccharides, As prebiotics exploit non-viable food ingredients, their applicability in diets is wide ranging, As gastrointestinal disorders are prevalent in terms of human health, both probiotics and prebiotics serve an important role in the prophylactic management of various acute and chronic gut derived conditions, Examples include protection from gastroenteritis and some inflammatory conditions
Archived at 2016/04/21